Formación de la infraestructura política para una reforma agraria radical: Adalberto Tejeda y la cuestión municipal en Veracruz, 1928-1932 - Ginzberg, Eitan (El Colegio de México, A.C., 2000)
This paper is about the struggle for municipal dominion in the state of Veracruz in 1928-1932. The need for such dominion became a sine qua non condition and derived directly from the agrarianism of state Governor Adalberto Tejeda, who thereby attempted to create an irreversible socioeconomic reality. Such a condition had five main causes: the nature of Tejeda's agrarianism, based on the state's initiative and  the municipalities' executive powers; the complex geopolitical structure of Veracruz, due to which Jalapa depended on municipal actions in order to exert its control; the opposition of businessmen and industrialists, as well as of potential supporters within the urban workers' movement, all well-known in regional centers: Tejeda's idea that direct and constant struggle (between the State and conservative municipalities) was vitally necessary in shaping a popular revolutionary awareness; and the powerful role attributed to municipal authorities in the alternate ultra-federate model (or "trilogy") that Tejeda proposed for Mexico. For these  and other reasons, Tejeda devoted the four years of  his government to a hard fought struggle  for municipal dominion, which triumphed in 1931. This victory got Tejeda very close  to the socioeconomic goal he had established at the onset of his government, and its influence is still felt today.